2020
DOI: 10.26418/jaakfe.v9i1.41143
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Mempengaruhi Kualitas Laporan Keuangan Pemerintah Daerah Dengan Sistem Pengendalian Internal Pemerintah Sebagai Pemoderasi (Studi Empiris Pada Opd Dikabupaten Kuburaya)

Abstract: Tujuan dari penelitian ini adalah untuk menguji pengaruh kompetensi sumber daya manusia, standar akuntansi pemerintahan dan sistem akuntansi keuangan daerah terhadap kualitas laporan keuangan pemerintah daerah dengan sistem pengendalian internal pemerintah sebagai pemoderasi. Data yang digunakan dalam penelitian ini adalah data primer. Metode pengumpulan data dilakukan dengan memberikanpertanyaan tertulis berupa kuesioner kepada responden. Populasi penelitian ini adalah seluruh pegawai bagian keuangan yang ber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 1 publication
5
8
0
Order By: Relevance
“…However, the fact is that the current internal control system is not optimal in terms of controlling the activities that have been carried out by the village apparatus because there is still a misappropriation of village funds. The results of this study are supported by research results (Kapriana and Agung, 2020) found that the internal control system was unable to moderate the relationship between government accounting standards and the quality of financial reports. The internal control system has not been able to supervise the compliance of financial officials in preparing reports on time and according to standards.…”
Section: The Effect Of Internal Control System On Characteristics Of ...supporting
confidence: 72%
See 1 more Smart Citation
“…However, the fact is that the current internal control system is not optimal in terms of controlling the activities that have been carried out by the village apparatus because there is still a misappropriation of village funds. The results of this study are supported by research results (Kapriana and Agung, 2020) found that the internal control system was unable to moderate the relationship between government accounting standards and the quality of financial reports. The internal control system has not been able to supervise the compliance of financial officials in preparing reports on time and according to standards.…”
Section: The Effect Of Internal Control System On Characteristics Of ...supporting
confidence: 72%
“…Research from (Prasetya et al, 2017) found that supervision positively affects the quality of Village Financial System implementation. The better the supervision, the better the implementation of the Village Financial System system and has implications for the quality of financial reports (Kapriana and Agung, 2020) found that the government's internal control system was able to moderate H4 H2 H5…”
Section: Theoritical Reviewmentioning
confidence: 99%
“…A study of government internal control systems will reduce the impact of the implementation of regional accounting standards on the quality of local government financial reports. Kapriana & Agung (2020) moderated findings on government internal control systems. The impact of regional financial accounting systems on the quality of financial reports contrasts with the findings of Nuraini et al (2019) and Laoli & Mukti (2022) find that government internal control systems have failed to mitigate the relationship between the quality of local government financial reporting and the implementation of government accounting standards.…”
Section: Introductionmentioning
confidence: 92%
“…Another study examines the relationship between the implementation of regional accounting standards and the quality of local government financial reports. Kapriana & Agung (2020), Nuraini et al (2019), Philadhelphia et al (2020), andHarahap et al (2018) concluded that local accounting standards influence the quality of local government financial reporting. The impact of using a regional financial accounting system on the quality of local government financial reports was examined by Setiawan et al (2021), Maydiyanti et al (2020), Defitri (2018), andHusna (2022) contain research findings of local financial accounting systems that have a significant impact on the quality of local government financial reporting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation